Faktor Risiko yang Berhubungan dengan Kejadian Anemia pada Remaja Putri - Mahmut Jaelani; Betty Yosephin Simanjuntak; Emy Yuliantini (Politeknik Kesehatan Tanjung Karang, 2017)
Teenage girls are one of the groups who are prone to anemia. Anemia in teenage girls is still a big public health problem because the prevalence is still ≥20% that is equal to 21,7%. This study aimed to examine the dominant factors associated with the incidence of anemia and determinants in teenage girls in MTsN 02 Kota Bengkulu with a cross-sectional design. The population was all female adolescents in MTsN 02 Kota Bengkulu and the sample was taken by using simple random sampling as much as 100 respondents taken from class VII and class VIII. The results showed that the anemia was 33.0% and there was a relationship between menstrual period (p=0,028), nutritional status (p=0,000), breakfast habits (p=0,000), iron intake (p=0,000), intake protein (p=0,017), consumption pattern of iron absorption inhibitor (p=0,045) and there was no significant correlation between maternal education level (p=0,265) with incidence of anemia in Young women at MTsN 02 Kota Bengkulu. Variable nutritional status is the most dominant associated anemia in young women.